Acessibilidade arquitetônica nos nove principais hospitais públicos na microrregião do vale do Açu - Fernandes, Rilka Cellys da Silva (Universidade Federal Rural do Semi-Árido, 2019)
This work aims to raise the basic accessibility items in public hospitals in the Vale in Açu microregion, Rio Grande do Norte, Brazil. The research is a qualitative and quantitative case study carried out between December 2018 and January 2019 to map the main public hospital of each of the nine municipalities that make up the micro-region studied and verify the presence of basic items of accessibility in the building of each one of them. Data were collected through: visits to nine basic units; and questionnaires applied to their employees and patients with some reduced mobility or physical disability (temporary or permanent). Of the 20 (twenty) items observed throughout the analysis, only one of them was found in all the units visited, which arethe ramps on the sidewalks. This result is enough to realize and conclude that there is no accessibility in the health care buildings of the microregion of the Vale in Açu. And that, therefore, there are physical and architectural barriers that compromise the right of access of many people to public health services. The lack of knowledge of the people about the conceptualization of the subject, and the lack of inspection by the population itself and of the instituted powers contribute to the existence of this inaccessibility.
Artigo Acadêmico
Keywords: Acessibilidade arquitetônica; Hospital público; Saúde; Accessibility; Architectural; Public hospital; Cheers; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA